Numerical Modelling of Oil Spills in the Area of Kvarner and Rijeka Bay (The Northern Adriatic Sea) - Goran Lončar; Gordana Beg Paklar; Ivica Janeković (Journal of Applied Mathematics)
Several hypothetical cases of oil spills from tankers in the Kvarner and Rijeka Bay were analyzed using three-dimensional circulation models coupled with oil spill model. Two circulation models—local one covering the area of Kvarner Bay, Rijeka Bay, and Vinodol channel along with the basin-wide one covering the whole Adriatic Sea—are connected through the one-way nesting procedure by imposing the results from the Adriatic model to the open boundaries of the local one. Oil spill model relays on the current fields obtained by the local circulation model during all our simulations. Spreading of the oil pollution from three hypothetical positions of tanker accidents in the local model domain was simulated for the periods of 10 “winter-season” and “summer-season” days. The oil spill model results show that the hypothetical tanker accidents in the center of the Rijeka Bay are the most dangerous for the studied area in both seasons. Summer-season case shows significantly worse situation from the ecological point of view, oil spills spread on the larger area simply because stratification and mixing present during the winter period reduce oil slick effect.